The Expanded Shadow Theater. My experience with the Lumiato Cía (A Luz em Cena: Revista de Pedagogias e Poéticas Cenográficas, 2024)
During the years 2023 and 2024 I accompanied the Lumiato Company of Brasilia in creative processes that expanded the language of shadow theater and resulted in two scenic experiences: an interactive object installation and a shadow show, theater and dance. The theme that ran through these processes was the family legacy of care granted to women for several generations and how this hindered their subsequent development. The process of this experience and its frame of reference is written in this article
Keywords: Key Words Shadow Theatre Artistic Installation Feminism Archive Movement